A Meta-Analysis on Developing Effective Hots Questioning Skills for Stem Teachers in Malaysia - Khairuddin, Nor’Aida; Talib, Rohaya; Atmareni Harmeni, Haiza; Radzali, Muhammad (International Journal of Psychosocial Rehabilitation, 2020)
In developing 21st-century skills, improvement of STEM education is in demand in most countries for solving complex global issues and global economic development. Effective questioning skills by STEM teachers could help to engage and scaffold students in learning and higher-level thinking processes. However, most STEM teachers in Malaysia still applied lower-order and closed-ended questions in teaching and learning sessions because of their lack of knowledge and skills in HOTS questioning. This paper provided an overview of effective strategies to develop HOTS questioning skills. The research methodology was based on a literature review search strategy through ERIC and online databases and journals such as EBSCOhost, ScienceDirect, Scopus, SpringerLink, Web of Science (WoS), SAGE, Taylor & Francis Online, and Wiley Online Library. The keywords used for this research were STEM education, questioning skills, higher-order thinking skills (HOTS), and STEM pedagogical development. From the meta-analysis, the results showed that the promote inquiry approach, proper wait time, pedagogical content knowledge, and recognition were the dominant strategies in questioning, which helped to develop students’ cognitive and HOTS abilities. Findings from this review will guide the STEM teachers to enhance their pedagogical skills, especially in HOTS questioning, and strengthen the quality of STEM education in the future.